Improving Health Industries by the Supply-Chain Policy - Kozhina, Y. A; Frolovskaya, Y. I; Yudina, Y. V; Yunusova, K. V; Makhiboroda, M. N (International Journal of Supply Chain Management, 2020)
Abstract— the article deals with issues of the policy in the sphere of protection of a Supply-Chain management’s rights and legitimate interests in the health centres. The issues of protection of the rights of Supply-Chain management in the field of health care revealed. In today's global and national economy, businesses are increasingly relying on outsourcing some of their activities and processes. Therefore, more and more companies at the Supply-Chain level, in specific networks, operate and compete with their suppliers and service providers. This process of outsourcing and the growing importance of supply chains has its consequences in the working conditions and health and safety of workers of supply companies and contractors. There are two main networks of Supply-Chain or relationships between companies and members of their supply chain: the main network (a company and suppliers of its specific goods and materials) and the secondary network (a company and its contractors and subcontractors special services such as activities Maintenance, construction, cleaning or catering This report provides an overview, analysis, conclusions and recommendations on how to upgrade health centers through the above Supply-Chain networks.